Extraction, bioevaluation and characterization of soybean and locust bean seeds proteins as plant-based meat substitutes - Sadiya Alka; Halima Bawa; Muhammad Jamilu Dauda; Sulaiman Mohammed; Ahmed Olatunde; Jamila Salihu; Khadija Aliyu Nuru; Misbahu Abdullahi Tahir; Eloanyi Sylvester Ikenna; Akinwoye Rukayat Oyefunke (Regulatory Toxicology and Pharmacology, 2026)

Generational selection, transcriptomics and functional characterization reveal the impact of environmental pollutants on the evolution of insecticide resistance in malaria vectors - Abdullahi Muhammad; Sulaiman S. Ibrahim; Helen Irving; Talal Al-Yazeedi; Jack Hearn; Mark J.I. Paine; Charles S. Wondji (Insect Biochemistry and Molecular Biology, 2026)

Per- and polyfluoroalkyl substances: Environmental occurrence, health impacts, and advanced removal technologies - Mustapha Saheed; Mohsen Salma; Usman Abdullahi Rakiya; Abubakar Ladio Hassana; Lukman Asiya Muhammad; Jimoh Oladejo Tijani; Ambali Saka Abdulkareem; Muhammad Muhammad Ndamitso; Kehinde Shola Obayomi; Guillermo Díaz-Sainz; Jianhua Zhang (Colloids and Surfaces C: Environmental Aspects, 2026)

Multi-mycotoxin contamination, dietary exposure and health risk assessment of maize consumed in Niger State, Nigeria - Fatimah Omolola Badmos; Maimuna Abdullahi Habib; Victor Tope Oyetunji; Achi Dabara; Hadiza Kudu Muhammad; Abdullahi Abdulkadir; Susan Salubuyi; Daniel Ojochenemi Apeh; Maurice Monjerezi; Limbikani Matumba; Mulunda Mwanza; Hussaini Anthony Makun (Mycotoxin Research, 2026)

Assessment of effective dose and radiation risk due to 226Ra, 40K, and 232Th exposure within the soil of artisanal gold mine using the RESRAD code - Abdullahi Muhammad; Akbar Abbasi (Environmental Monitoring and Assessment, 2026)

Climate-resilient livestock systems in Sub-Saharan Africa: a one health systems framework integrating pastoralism, animal health, and sustainable development - Muhammad Yasir Alhassan; Abdulhamid Abdullahi Ahmad; Mubarak Aliyu Danmaraya (Tropical Animal Health and Production, 2026)

Polymeric membrane technologies for wastewater treatment and valorization: Advancing sustainable and circular water systems - Mustapha Saheed; Usman Benedict Shama; Abdullahi Karimatu Lami; Elijah Yanda Shaba; Kehinde Shola Obayomi; Awe Omoniyi Babajide; Jimoh Oladejo Tijani; Ambali Saka Abdulkareem; Muhammad Muhammad Ndamitso (Journal of Environmental Sciences, 2026)

Parental Iron Deficiency Programs Oxidative Stress and Epigenetic Demethylase Dysregulation (TET and KDM2) in Drosophila melanogaster Offspring - Farida Bashar; Kasimu Ghandi Ibrahim; Abdullahi Yahaya Abbas; Muhammad Bashir Bello; Mustapha Umar Imam; Aliu Abdulhameed Zubair (Biological Trace Element Research, 2026)

Widespread Use of Banned Pesticides and Weak Regulatory Enforcement: Environmental and Health Implications Among Farmers in Gombe State, Nigeria - Mohammad Bashir Sulaiman; Babangida Hammani; Abdullahi Muhammad Gimba; Oluyinka Omoyeni Akinlotan; Aliyu Tijjani Fadawa; Umar Musa Kwami; Taibatu Idris Umar; Amina Muhammad Bello (Journal of Agromedicine, 2026)

Machine and deep learning for sentinel-based land use and land cover change detection: a systematic review and future outlook - Anam Nigar; Yang Li; Muhammad Yousuf Jat Baloch; Sedra Shafi; Abdullahi Garba Usman (Environmental Monitoring and Assessment, 2026)

Assessing the impact of agricultural greenhouse gas emissions, financial development, and land use on cereal production in Sub-Saharan Africa: an econometric and machine learning approach - Abubakar Sabo Ahmad; Nazir Muhammad Abdullahi; Umar Shehu Umar; Bello Nasiru Abdullahi; Abdulaziz Nuhu Jibril; Amina Barau Inuwa; Mustapha Muhammad (Environment, Development and Sustainability, 2026)

SARS-CoV-2 antibody responses during the omicron wave in kano, nigeria: Implications for strengthening future vaccine strategies - Bilkisu Ahmed; Jamilu Abubakar Bala; Taysir Ramadan Hafiz; Isah Abubakar Aliyu; Abdulhadi Sale Kumurya; Ibrahim Muhammad Badamasi; Hayatu Saidu; Muhammad Adamu Abbas; Auwal Idris Kabuga; Alhassan Sharif Abdullahi; Bashiru Garba; Al-Mukhtar Yahuza Adamu; et al. (Next Research, 2026)

Numerical simulation of breakdown threshold voltage in charging coils of wireless power transfer systems - Umar Musa; Abdullahi Abubakar Mas’ud; Johnatan M. Rodríguez-Serna; Abdullahi Mohammad; Muhammad Lotfi Hussain; Firdaus Muhammad-Sukki (Next Research, 2026)

Health risk assessment of radon exposure through drinking water in Iluagba, Kogi State, Nigeria - Ibrahim Ayodeji Bello; Abdullahi Muhammad Vatsa; Hameed Adavize Momoh; Taiwo Abadunmi; A. A. Bello (Isotopes in Environmental and Health Studies, 2026)

Wet-dry rotation plus straw mulching alleviates soil secondary salinization, nitrogen leaching, cucumber Fusarium wilt and net global warming potential - Zijian Zheng; Wangpei Zhou; Xiaoping Zeng; Xueshuang Gao; Feng Ding; Jinjun Ma; Zhiping Zhang; Jiexia Liu; ABDULLAHI MUHAMMAD WAIYA; Minmin Miao (Plant and Soil, 2026)

Challenging Evolutionary Paradigms: Daphnia Populations Resurrected From Unpolluted Environments Show Enhanced Detoxification Ability to Aromatic Pollutants - Florian Gigl; Muhammad Abdullahi; Sam Benkwitz‐Bedford; Niamh Eastwood; Jiarui Zhou; Henner Hollert; Luisa Orsini (Molecular Ecology, 2026)
Understanding how organisms respond to chemical stress requires disentangling genetically encoded (constitutive) adaptations from environmentally induced (plastic) responses. This challenge is particularly acute for polycyclic aromatic hydrocarbons (PAHs), widespread aquatic pollutants with well‐documented toxicity, where mechanisms of tolerance, including host–microbiome interactions, are unexplored. We used Daphnia magna , a keystone freshwater species with clonal reproduction and dormant egg banks to test population‐specific (constitutive) responses to phenanthrene (PHE), a common PAH. Populations resurrected from contrasting historical environments were exposed to sub‐lethal PHE concentrations, and both host transcriptomes and gut microbiomes were profiled to assess induced responses. Transcriptomic analysis revealed distinct, population‐specific responses in detoxification, stress signalling, and endocrine regulation. Unexpectedly, the semi‐pristine (pollution‐naïve) population showed higher tolerance, with robust induction of cytochrome P450 and hormonal pathways, while populations historically exposed to pollution exhibited chronic stress signatures and reduced plasticity. Gut microbiome profiling revealed PHE‐induced functional shifts across populations, with the pollution‐naïve population showing broader stress‐associated responses and historically exposed populations to pollutants exhibiting more detoxification‐focused microbiome profiles. Both host and microbial datasets consistently showed enrichment in pyruvate and carbon metabolism, indicating coordinated energy mobilisation and detoxification responses. Our results show that historical exposure to chemical stress and wider pollution does not necessarily confer enhanced physiological tolerance to PHE. Instead, hydrocarbon stress elicits coordinated, functionally linked responses across the host and its associated microbiome. By leveraging Daphnia 's unique ecology and evolutionary history, we disentangle constitutive from plastic responses and show that microbiome functional reconfiguration under PHE exposure is coordinated with host responses, contributing to population‐specific profiles.

Provenance, diagenesis and reservoir quality of the Aptian-Albian Bima sandstone, Upper Benue Trough, NE Nigeria - Yusuf Abdullahi Abdulkarim; Abdulwahab Muhammad Bello; Khalid Al-Ramadan (Journal of African Earth Sciences, 2026)

Genetic Mapping of Resistance: ddRADseq ‐Based QTL and Associated Polymorphism Conferring Resistance to Alpha‐Cypermethrin in Anopheles funestus - Talal Al‐Yazeedi; Grâce Djuifo; Leon M. J. Mugenzi; Abdullahi Muhammad; Helen Irving; Jack Hearn; Charles S. Wondji (Molecular Ecology, 2026)
The heavy reliance on pyrethroid‐based interventions has largely driven insecticide resistance in malaria vectors, accelerating the spread of resistant strains, including resistant Anopheles funestus strains. The efficacy of insecticide‐based interventions, especially insecticide‐treated nets (ITNs), the cornerstone of malaria control and management, is threatened by the widespread occurrence of resistance, jeopardising malaria control efforts. Alpha‐cypermethrin, a type II pyrethroid, is increasingly utilised in various ITN formulations, including those combined with piperonyl butoxide (PBO) and chlorfenapyr‐based Interceptor G2 (IG2) nets, to enhance effectiveness against resistant mosquito populations. Therefore, understanding the molecular basis of resistance is essential to monitor and track resistance trends for an effective malaria control program. In this study, we identified a 1.4 Mb QTL on the telomeric end of the left arm of chromosome 2, conferring resistance to α‐cypermethrin ( rap1 QTL). Different crossing schemes and sequencing approaches were explored to determine the most effective strategy. Individual‐based QTL mapping performed on segregating individuals from an isofemale family identified a QTL at the F 7 generation. Higher recombination density relative to the physical genome in the F 7 isofemale family, with a recombination every 240 kb, facilitated the detection of a QTL compared to the F 2 family (335 kb/cM). Additionally, we exploited bulk segregant analysis (BSA) between susceptible and resistant phenotypes from the F 7 isofemale family and an F 7 mixed cross‐family to perform cost‐effective and rapid QTL‐mapping discovery. The strongest signal in both independent BSA analyses overlaps with the rap1 QTL, further supporting its role in α‐cypermethrin resistance. The known resistant alleles of the cytochrome P450 CYP6P9a and 6.5‐kb structural variant within the rap1 QTL strongly correlate with survival to α‐cypermethrin. In this study, we validated that previously developed DNA‐based assays, originally designed to monitor permethrin resistance, are effective for tracking resistance to α‐cypermethrin as well. Additionally, we identified candidate variants that can serve as reliable markers for monitoring α‐cypermethrin resistance.

Advances in bacterial chromium biosorption: current perspectives and future directions - Abdullahi Adamu Faggo; Bashar Haruna Gulumbe; Nazeef Idris Usman; Tirmizhi Munkaila Abubakar; Kadai Alhaji Lawan; Musbahu Abdullahi Bagwai; Kabir Hassan Sambo; Muhammad Bello; Mubarak Hassan Ismail; Wada Nafiu (Environmental Science and Pollution Research, 2025)

In silico identification of GTPase inhibitors from selected anti-gonorrheal plants against Neisseria gonorrhoeae - Blessing O. Awoyemi; Badmus Jamiu Damilare; Abdullahi Tunde Aborode; Che Muhammad Khairul Hisyam Ismail; Abdulqohar Adebayo; Haruna Isiyaku Umar; Ibrahim Akindeji Makinde; Ridwan Opeyemi Bello; Sodiq Fakorede; Mohammed M. Alshehri; Ahmed F. Alanazi (The Nucleus, 2025)

Computer-aided design process of possible antisickling agents using molecular docking, pharmacokinetic assessment, homology modeling, and molecular dynamic studies targeting Hba protein - Stephen Ejeh; Habiba Asipita Otaru; Muhammad Tukur Ibrahim; Abdullahi Bello Umar; John Enyi Ejeh; Abduljelil Ajala; Samuel Ndaghiya Adawara; Ramith Ramu; Fabian Audu Ugbe; Joshua John; Idongesit Bassey Anweting (In Silico Pharmacology, 2025)

Spatiotemporal dynamics of the interactions between urban surface temperature and extreme hourly rainfall in Nigerian cities - Khalid Sulaiman; Mohd Ridza Mohd Haniffah; Al-Amin Danladi Bello; Mohd Khairul Idlan Muhammad; Shamsuddin Shahid; Abdullahi Sule Argungu; Bashir Tanimu (Theoretical and Applied Climatology, 2025)

Geostatistical and multivariate analysis of phosphate evolution and its relationship with heavy metals in shallow groundwater in a Semi-Arid Basin - Saadu Umar Wali; Noraliani Binti Alias; Abdulqadir Abubakar Usman; Abdullahi Umar; Nasiru Muhammad; Ismail Usman Kaoje; Buhari Samaila; Basiru Aliyu; Habiba Muhammad Ladan; Mudassiru Atiku; Sa’ad Ibrahim (Earth Science Informatics, 2025)

Quantitative structure–activity relationship (QSAR) hazard assessment of the banned pesticides by the National Agency for Food and Drugs Administration and Control - Hashim Ndaman Muhammad; Abdullahi Sani Yahaya; Hamdalat Folake Muritala (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Malaria parasite detection in Red Blood Cells with rouleaux formation morphology using YOLOv9 - Fatima Abdullahi Muhammad; Rubita Sudirman; Nor Aini Zakaria (Tissue and Cell, 2025)

Optimization of Extreme Learning Machine with Metaheuristic Algorithms for Modelling Water Quality Parameters of Tamburawa Water Treatment Plant in Nigeria - Sani I. Abba; Quoc Bao Pham; Anurag Malik; Romulus Costache; Muhammad Sani Gaya; Jazuli Abdullahi; Sagiru Mati; A. G. Usman; Gaurav Saini (Water Resources Management, 2025)

Mathematical analysis of chickenpox population dynamics unveiling the impact of booster in enhancing recovery of infected individuals - Kabiru Garba Ibrahim; James Andrawus; Abbas Abubakar; Abdullahi Yusuf; Stephen Ishaya Maiwa; Kefas Bitrus; Muhammad Sani; Ibrahim Abdullahi; Sunday Babuba; Joseph Jonathan (Modeling Earth Systems and Environment, 2025)

Horticultural postharvest loss’ and its socio-economic and environmental impacts - Abdelrahman Ali; Yanwen Tan; Khalid Medani; Chunping Xia; Nazir Muhammad Abdullahi; Irfan Mahmood; Shilong Yang (Journal of Environmental Management, 2025)

CMIP5 and CMIP6: contrasting perspectives on Nigeria’s climate transformation - Bashir Tanimu; Mohammed Magdy Hamed; Al-Amin Danladi Bello; Sule Argungu Abdullahi; Morufu A. Ajibike; Zaher Mundher Yaseen; Ahmed Abdiaziz Alasow; Mohd Khairul Idlan bin Muhammad; Shamsuddin Shahid (Theoretical and Applied Climatology, 2025)

Advancing plant disease classification: A robust and generalized approach with transformer-fused convolution and Wasserstein domain adaptation - Muhammad Hanif Tunio; Jian ping Li; Xiaoyang Zeng; Awais Ahmed; Syed Attique Shah; Hisam-Uddin Shaikh; Ghulam Ali Mallah; Imam Abdullahi Yahya (Computers and Electronics in Agriculture, 2024)

Combined toxicity of perfluoroalkyl substances and microplastics on the sentinel species Daphnia magna: Implications for freshwater ecosystems - Tayebeh Soltanighias; Abubakar Umar; Muhammad Abdullahi; Mohamed Abou-Elwafa Abdallah; Luisa Orsini (Environmental Pollution, 2024)

Improving Short-term Daily Streamflow Forecasting Using an Autoencoder Based CNN-LSTM Model - Umar Muhammad Mustapha Kumshe; Zakariya Muhammad Abdulhamid; Baba Ahmad Mala; Tasiu Muazu; Abdullahi Uwaisu Muhammad; Ousmane Sangary; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Mosaad Ali Hussein Ali; Aliyu Uthman Bello; Muhammad Muhammad Bala (Water Resources Management, 2024)

Correction to: Enhanced streamflow forecasting using attention-based neural network models: a comparative study in MOPEX basins - Abdullahi Uwaisu Muhammad; Tasiu Muazu; Haihua Ying; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Aliyu Uthman Bello; Muhammad Muhammad Bala; Mosaad Ali Hussein Ali; Umar Sani Dabai; Umar Muhammad Mustapha Kumshe; Muhammad Sabo Yahaya (Modeling Earth Systems and Environment, 2024)

Interactions between phenanthrene exposure and historical chemical stress: Implications for fitness and ecological resilience of the sentinel species Daphnia magna - Florian Gigl; Muhammad Abdullahi; Marianne Barnard; Henner Hollert; Luisa Orsini (Science of The Total Environment, 2024)

Analyses of oxidative DNA damage among coal vendors via single cell gel electrophoresis and quantification of 8-hydroxy-2’-deoxyguanosine - Ali Sani; Ibrahim Lawal Abdullahi; Muhammad Idrees Khan; ChengXi Cao (Molecular and Cellular Biochemistry, 2024)

Enhanced streamflow forecasting using attention-based neural network models: a comparative study in MOPEX basins - Abdullahi Uwaisu Muhammad; Tasiu Muazu; Haihua Ying; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Aliyu Uthman Bello; Muhammad Muhammad Bala; Mosaad Ali Hussein Ali; Umar Sani Dabai; Umar Muhammad Mustapha Kumshe; Muhammad Sabo Yahaya (Modeling Earth Systems and Environment, 2024)

Morphological and physiological features in small ruminants: an adaptation strategy for survival under changing climatic conditions - Abubakar Danmaigoro; Mahmud Abdullahi Muhammad; Kabeer Abubakar; Royford Bundi Magiri; Archibold Garikayi Bakare; Paul Ade Iji (International Journal of Biometeorology, 2024)

Unveiling the interconnected dynamics of urbanization, energy consumption, and food exports: assessing carbon emissions with an innovative ARDL approach - Nazir Muhammad Abdullahi; Abdelrahman Ali; Yue Wang; Shayan Khan Kakar; Jafir Mehmood; Xuexi Huo (Environment, Development and Sustainability, 2024)

Enhancing reliability in climate projections: A novel approach for selecting global climate models - Bashir Tanimu; Al-Amin Danladi Bello; Sule Argungu Abdullahi; Morufu A. Ajibike; Mohd Khairul Idlan bin Muhammad; Shamsuddin Shahid (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Comparison of conventional and machine learning methods for bias correcting CMIP6 rainfall and temperature in Nigeria - Bashir Tanimu; Al-Amin Danladi Bello; Sule Argungu Abdullahi; Morufu A. Ajibike; Zaher Mundher Yaseen; Mohammad Kamruzzaman; Mohd Khairul Idlan bin Muhammad; Shamsuddin Shahid (Theoretical and Applied Climatology, 2024)

Identification of novel laccase from cyanobacterium Microcystis flos-aquae and enhanced azo dye bioremediation potential - Muhammad Ayyub Muhammad; Emmanuel Oluwadareus Balogun; Abdullahi Balarabe Sallau; Mathias Ahii Chia; Mohammed Nasir Shuaibu (Bioresource Technology, 2024)

Dynamic linkages between financial development, economic growth, urbanization, trade openness, and ecological footprint: an empirical account of ECOWAS countries - Nazir Muhammad Abdullahi; Adamu Ali Ibrahim; Qiangqiang Zhang; Xuexi Huo (Environment, Development and Sustainability, 2024)

Marine Streptomyces sp. PGC 39: A treasure trove of new antimicrobial agents, macrolidycin, and pyrachlomycin - Rabbia Ahmad; Muhammad Imran Tousif; Mamona Nazir; Asma Yaqoob; Syed Adnan Ali Shah; Gokhan Zengin; Abdullahi Ibrahim Uba; Shabbir Muhammad (Food Bioscience, 2024)

Assessment of dietary exposure and levels of mycotoxins in sorghum from Niger State of Nigeria - Fatimah Omolola Badmos; Hadiza Lami Muhammad; Achi Dabara; Funmilola Adefolalu; Susan Salubuyi; Abdullahi Abdulkadir; Victor Tope Oyetunji; Daniel Ojochenemi Apeh; Hadiza Kudu Muhammad; Mulunda Mwanza; Maurice Monjerezi; Limbikani Matumba; et al. (Food Additives & Contaminants: Part A, 2024)

Harnessing water fleas for water reclamation: A nature-based tertiary wastewater treatment technology - Muhammad Abdullahi; Iestyn Stead; Sophie Bennett; Rafael Orozco; Mohamed Abou-Elwafa Abdallah; Sara Jabbari; Lynne E. Macaskie; Alexandra Tzella; Stefan Krause; Bushra Al-Duri; Robert G. Lee; Ben Herbert; et al. (Science of The Total Environment, 2023)

Analysis of land use and land cover change using machine learning algorithm in Yola North Local Government Area of Adamawa State, Nigeria - Auwal Aliyu; Muhammad Isma’il; Sule Muhammad Zubairu; Ibrahim Yahaya Gwio-kura; Abubakar Abdullahi; Babakaka Abdulsalam Abubakar; Muntaka Mansur (Environmental Monitoring and Assessment, 2023)

An autoencoder-based stacked LSTM transfer learning model for EC forecasting - Abdullahi Uwaisu Muhammad; Hamza Djigal; Tasiu Muazu; Jibril Muhammad Adam; Abdoul Fatakhou Ba; Umar Sani Dabai; Sani Tijjani; Muhammad Sabo Yahaya; Aliyu Ashiru; Umar Muhammad Mustapha Kumshe; Saddam Aliyu; Faruwa Ajibola Richard (Earth Science Informatics, 2023)

A bioactive chalcone from the aerial parts of Indigofera conferta Gillet - Maryam Isah; Salima Murtala; Sakynah Musa Abdullahi; Asmau Nasiru Hamza; Nasir Tajuddeen; Mu’ammar Lawal Dauda; Vuyisa Mzozoyana; Aliyu Muhammad Musa (Natural Product Research, 2023)

Comparative cyto-genotoxicity and clastogenicity properties of traditional trypanocidal Afrormosia laxiflora and Lonchocarpus laxiflorus plants in Wistar rats - Lovina Chinyere Ogbu; Aliyu Muhammad; Mohammed Aliyu Usman; Musa Bashir; Abdullahi Balarabe Sallau (Toxicology and Environmental Health Sciences, 2023)

Iron deficiency and its epigenetic effects on iron homeostasis - Bashar Farida; Kasimu G. Ibrahim; Bilyaminu Abubakar; Ibrahim Malami; Muhammad B. Bello; Murtala B. Abubakar; Abdullahi Y. Abbas; Mustapha U. Imam (Journal of Trace Elements in Medicine and Biology, 2023)

Transfer learning for streamflow forecasting using unguaged MOPEX basins data set - Abdullahi Uwaisu Muhammad; S. I. Abba (Earth Science Informatics, 2023)

Bioactive Peptides from African Yam (AVIAIMF and GPADPF) and Taro (NGDF and NGNW) Reveal Multifunctional Antidiabetic Effects Using Biochemical and Cellular Models - Mohammed Auwal Ibrahim; June Cheptoo Serem; Aliyu Dantani Abdullahi; Suleiman Aminu; Abubakar Babando Aliyu; Aliyu Muhammad Musa; Bashir Musa; Megan J. Bester; Anabella R. M. Gaspar (International Journal of Peptide Research and Therapeutics, 2023)

Performance of the 20 minutes Whole Blood Clotting Test in detection, monitoring and antivenom therapy of West African Carpet viper (Echis romani) envenoming in resource constrained settings in Nigeria - Muhammad Hamza; Titus B. Dajel; Saidu B. Abubakar; Auwalu S. Hamza; Hadiza L. Abdullahi; Garba Iliyasu; Abdulrazaq G. Habib (Toxicon, 2023)

Effect of waste cooking oil on warm mix asphalt block pavement – A comprehensive review - Yusuf Babangida Attahiru; Azman Mohamed; Ahmed Eltwati; Aliyu Abubakar Burga; Abubakar Ibrahim; Abdullahi Muhammad Nabade (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

A multifunctional key to open a new window on the path to natural resources-lessons from a study on chemical composition and biological capability of Paeonia mascula L. from Turkey - İnci Kurt-Celep; Gokhan Zengin; Engin Celep; Stefano Dall’Acqua; Stefania Sut; Irene Ferrase; Gunes Ak; Abdullahi Ibrahim Uba; Rıdvan Polat; Deniz Canlı; Ekrem Darendelioglu; Muhammad Zakariyyah Aumeeruddy; et al. (Food Bioscience, 2023)

Pollution profile, ecological and health risk assessment of trace metals in soils of auto mechanic workshops at Gombe metropolis, Gombe State, Northeastern Nigeria - Mohammad Bashir Sulaiman; Aishatu Hussein Santuraki; Abdullahi Muhammad Gimba; Sulaiman Babayo Ali; Aishatu Umar Barambu (Arabian Journal of Geosciences, 2022)

Pollution of heavy metal threat posed by e-waste burning and its assessment of human health risk - Ahmed Abubakar; Aminu Sulaiman Zangina; Ahmed Ibrahim Maigari; Murtala Muhammad Badamasi; Mohd Yusoff Ishak; Amina Sheikh Abdullahi; Jamilu Adamu Haruna (Environmental Science and Pollution Research, 2022)

Variations in the Serum Sialic Acid Profiles of Malaria Patients in Zaria, Nigeria: A Cross-Sectional Study - Mbateudi Danjuma Ika; Mohammed Auwal Ibrahim; Abdullahi Balarabe Sallau; Abdulmalik Abdullahi Salman; Abubakar Muhammad Sani; Murtala Bindawa Isah (Acta Parasitologica, 2022)

Historical exposure to chemicals reduces tolerance to novel chemical stress in Daphnia (waterflea) - Muhammad Abdullahi; Jiarui Zhou; Vignesh Dandhapani; Anurag Chaturvedi; Luisa Orsini (Molecular Ecology, 2022)
Until the last few decades, anthropogenic chemicals used in most production processes have not been comprehensively assessed for their risk and impact on wildlife and humans. They are transported globally and usually end up in the environment as unintentional pollutants, causing long‐term adverse effects. Modern toxicology practices typically use acute toxicity tests of unrealistic concentrations of chemicals to determine their safe use, missing pathological effects arising from long‐term exposures to environmentally relevant concentrations. Here, we study the transgenerational effect of environmentally relevant concentrations of five chemicals on the priority list of international regulatory frameworks on the keystone species Daphnia magna . We expose Daphnia genotypes resurrected from the sedimentary archive of a lake with a known history of chemical pollution to the five chemicals to understand how historical exposure to chemicals influences adaptive responses to novel chemical stress. We measure within‐ and transgenerational plasticity in fitness‐linked life history traits following exposure of “experienced” and “naive” genotypes to novel chemical stress. As the revived Daphnia originate from the same genetic pool sampled at different times in the past, we are able to quantify the long‐term evolutionary impact of chemical pollution by studying genome‐wide diversity and identifying functional pathways affected by historical chemical stress. Our results suggest that historical exposure to chemical stress causes reduced genome‐wide diversity, leading to lower cross‐generational tolerance to novel chemical stress. Lower tolerance is underpinned by reduced gene diversity at detoxification, catabolism and endocrine genes in experienced genotypes. We show that these genes sit within pathways that are conserved and potential chemical targets in other species, including humans.

Efficacy of stem cell secretome in the treatment of traumatic brain injury: A systematic review and meta-analysis of preclinical studies - Suleiman Alhaji Muhammad; Abdullahi Yahya Abbas; Mustapha Umar Imam; Yusuf Saidu; Lawal Suleiman Bilbis (Molecular Neurobiology, 2022)

Integrated management of Striga gesnerioides in cowpea using resistant varieties, improved crop nutrition and rhizobium inoculants - Wajiha M. Abdullahi; Mahamadi Dianda; Ousmane Boukar; Ibnou Dieng; Gaya S. Mohammed; Nouhoun Belko; Abou Togola; Hayat Muhammad; Fred Kanampiu; Ken E. Giller; Bernard Vanlauwe (Plant and Soil, 2022)
Background Cowpea is a grain legume of major importance in sub-Saharan Africa where it is cultivated by smallholder farmers on poor soils and production is often constrained by the parasitic weed Striga gesnerioides . Method Experiments were conducted to assess the potential of rhizobium inoculation to mitigate Striga infection and increase cowpea productivity. We infested soils with S. gesnerioides and assessed the impact of treatments combining cowpea genotypes and bradyrhizobium inoculation on Striga dynamics and cowpea yield. In total, 20 cowpea genotypes were included, of which nine were resistant to Striga and 11 were susceptible. In the first experiment these were factorially combined with three inoculation options (two bradyrhizobium strains USDA3384 and IRJ2180A, and uninoculated control) in a screen-house using potted sterile soils. Second, the same trial was repeated in the field with basal phosphorus applied at sowing and a fourth treatment of fertilizer-N (urea) included testing whether N was limiting cowpea growth. The field trial also included a separate treatment with no input that served as a negative check. Result Significant genotype x treatment interactions were observed in nodule counts, Striga attachment, emergence, and cowpea shoot growth in the screen-house. There were few nodules across all cowpea lines. Striga counts were the lowest for resistant varieties with no emerged plants. Rhizobial inoculants depressed Striga counts with consistent differences across cowpea genotypes. Inoculation with IRJ2180A performed the best against Striga attachment in resistant genotypes, and against Striga emergence in susceptible genotypes. In the field trial, cowpea grown without inputs had the least number of nodules. The genotype x treatment interaction was significant: resistant cowpea genotypes were free of emerged Striga while there was much more Striga emergence without input addition with susceptible genotypes. A significant genotype x treatment interaction was observed on cowpea grain yield. Yield response to inoculation was clearest with resistant genotypes inoculated with the strain IRJ2180A. Conclusion The integrated use of Striga -resistant cowpea lines, basal phosphorus fertilizer and elite bradyrhizobium inoculants is a promising approach to mitigate Striga infection and increase cowpea productivity.

Physical Modelling of Offshore Wind Turbine Foundations for TRL (Technology Readiness Level) Studies - Subhamoy Bhattacharya; Domenico Lombardi; Sadra Amani; Muhammad Aleem; Ganga Prakhya; Sondipon Adhikari; Abdullahi Aliyu; Nicholas Alexander; Ying Wang; Liang Cui; Saleh Jalbi; Vikram Pakrashi; et al. (Journal of Marine Science and Engineering, 2021)
Offshore wind turbines are a complex, dynamically sensitive structure due to their irregular mass and stiffness distribution, and complexity of the loading conditions they need to withstand. There are other challenges in particular locations such as typhoons, hurricanes, earthquakes, sea-bed currents, and tsunami. Because offshore wind turbines have stringent Serviceability Limit State (SLS) requirements and need to be installed in variable and often complex ground conditions, their foundation design is challenging. Foundation design must be robust due to the enormous cost of retrofitting in a challenging environment should any problem occur during the design lifetime. Traditionally, engineers use conventional types of foundation systems, such as shallow gravity-based foundations (GBF), suction caissons, or slender piles or monopiles, based on prior experience with designing such foundations for the oil and gas industry. For offshore wind turbines, however, new types of foundations are being considered for which neither prior experience nor guidelines exist. One of the major challenges is to develop a method to de-risk the life cycle of offshore wind turbines in diverse metocean and geological conditions. The paper, therefore, has the following aims: (a) provide an overview of the complexities and the common SLS performance requirements for offshore wind turbine; (b) discuss the use of physical modelling for verification and validation of innovative design concepts, taking into account all possible angles to de-risk the project; and (c) provide examples of applications in scaled model tests.

A novel antimicrobial flavonoid from the stem bark of Commiphora pedunculata (Kotschy & Peyr.) Engl. - Nasir Tajuddeen; Muhammad S. Sallau; Aliyu M. Musa; Sani M. Yahaya; James D. Habila; Abdullahi Musa Ismail (Natural Product Research, 2016)